Hyperimmunoglobulin D Syndrome: Case Report - Hacer ŞEN; Fatma SILAN; Emine BİNNETOĞLU and Fahri GÜNEŞ and Çisem AKURUT and Ahmet ULUDAĞ and Öztürk ÖZDEMİR (Archives of Rheumatology, 2015)
Hyperimmunoglobulin D syndrome is a rare autosomal recessive inherited disease characterized by fever attacks, which may be accompanied by chills, headache, abdominal pain, and cervical lymphadenopathy. Typical hyperimmunoglobulin D syndrome patients start to show symptoms in the first years of life. Diagnosis is based on the presence of symptoms with reduction in the enzyme activity of mevalonate kinase or by detecting the mutation in the mevalonate kinase gene that causes the disease. In this article, we present a 21-year-old female patient who started having fever attacks in early childhood and was diagnosed with familial Mediterranean fever; however, in spite of treatment, whose complaints did not resolve. The genetic analysis, which detected homozygote mevalonate kinase gene mutation and resulted in the hyperimmunoglobulin D syndrome diagnosis, is presented with an accompanying discussion of the literature.